Effects of acute estradiol and progesterone on perimenstrual exacerbation of suicidal ideation and related symptoms: a crossover randomized controlled trial - Eisenlohr-Moul, Tory A.; Bowers, Savannah M.; Prinstein, Mitchell J.; Schmalenberger, Katja; Walsh, Erin C.; Young, Steven L.; Rubinow, David R.; Girdler, Susan S. (Translational Psychiatry, 2022)
Female suicide attempts peak peri-menstrually - around the onset of menses - when the ovarian steroids estradiol (E2) and progesterone (P4) fall rapidly. Given preclinical evidence that withdrawal from either E2 or P4 can provoke behaviors consistent with elevated suicide risk, we hypothesized that withdrawal from one or both of these steroids contributes to perimenstrual exacerbation of suicidal ideation (SI) and related symptoms. In a randomized, controlled, double-blind crossover experiment (NCT03720847), a transdiagnostic sample of naturally cycling, medically healthy psychiatric outpatients reporting past-month SI completed two conditions during two different 14-day experimental intervals (days 7-20 where the luteinizing hormone surge = day 0), separated by a monthlong washout cycle. In the E2 and P4 (EP) condition, participants received transdermal E2 (0.1 mg/day) plus oral micronized P4 (200 mg/day as 100 mg twice daily) to buffer perimenstrual steroid withdrawal. A matched placebo (PBO) condition allowed natural perimenstrual steroid withdrawal. Participants reported daily SI and planning (primary outcomes) and indices of depression (low mood, hopelessness), threat sensitivity (anxiety, perceived stress), executive functioning (difficulty concentrating, impulsivity), and social cognitive bias (rejection sensitivity, perceived burdensomeness). In baseline cycles, no participant met prospective criteria for DSM-5 premenstrual dysphoric disorder, but 59% met all criteria except full follicular symptom remission, and 93% showed the highest SI in the perimenstrual phase. Of 29 randomized, 28 were analyzed (14 EP-PBO, 14 PBO-EP). Experimental administration of E2 and P4 (relative to PBO) reduced perimenstrual exacerbation of SI, suicide planning, depression, hopelessness, perceived stress, rejection sensitivity, and perceived burdensomeness, particularly in the perimenstrual (natural E2 and P4 withdrawal) days. Further, delayed withdrawal from experimental E2 and P4 (but not PBO) recapitulated SI, hopelessness, and rejection sensitivity. Acute perimenstrual withdrawal from ovarian steroids may play a causal role in perimenstrual worsening of depression and SI.
Gesehen am 08.02.2023